Medicinal plants and rituals. Magicotherapeutic and magicoprophylactic plant uses in Pallars (Pyrenees, Catalonia, Iberian Peninsula) - Agelet, Antoni; Vallès, Joan (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Medicinal plants and rituals. Magicotherapeutic and magicoprophylactic plant uses in Pallars (Pyrenees, Catalonia, Iberian Peninsula)